Comprehensive Nonclinical Safety Assessment of Nirmatrelvir Supporting Timely Development of the SARS-COV-2 Antiviral Therapeutic, Paxlovid™. (August 2022) - Sathish, Jean G.; Bhatt, Siddhartha; DaSilva, Jamie K.; Flynn, Declan; Jenkinson, Stephen; Kalgutkar, Amit S.; Liu, Maggie; Manickam, Balasubramanian; Pinkstaff, Jason; Reagan, William J.; Shirai, Norimitsu; Shoieb, Ahmed M.; et al.
COVID-19 is a potentially fatal infection caused by the SARS-CoV-2 virus. The SARS-CoV-2 3CL protease (Mpro) is a viral enzyme essential for replication and is the target for nirmatrelvir. Paxlovid (nirmatrelvir co-administered with the pharmacokinetic enhancer ritonavir) showed efficacy in COVID-19 patients at high risk of progressing to hospitalization and/or death. Nonclinical safety studies with nirmatrelvir are essential in informing benefit-risk of Paxlovid and were conducted to support clinical development. In vivo safety pharmacology assessments included a nervous system/pulmonary study in rats and a cardiovascular study in telemetered monkeys. Potential toxicities were assessed in repeat dose studies of up to 1 month in rats and monkeys. Nirmatrelvir administration (1, 000 mg/kg, p.o.) to male rats produced transient increases in locomotor activity and respiratory rate but did not affect behavioral endpoints in the functional observational battery. Cardiovascular effects in monkeys were limited to transient increases in blood pressure and decreases in heart rate, observed only at the highest dose tested (75 mg/kg per dose b.i.d; p.o.). Nirmatrelvir did not prolong QTc-interval or induce arrhythmias. There were no adverse findings in repeat dose toxicity studies up to 1 month in rats (up to 1, 000 mg/kg daily, p.o.) or monkeys (up to 600 mg/kg daily, p.o.). Nonadverse, reversible clinical pathology findings without clinical or microscopic correlates included prolonged coagulation times at ≥60 mg/kg in rats and increases in transaminases at 600 mg/kg in monkeys. The safety pharmacology and nonclinical toxicity profiles of nirmatrelvir support clinical development and use of Paxlovid for treatment of COVID-19.